Serrivomer jesperseni Bauchot 1953 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Serrivomer jesperseni Bauchot, 1953. Crossthroat Sawpalate. To 67 cm (26.8 in) SL (Mecklenburg et al. 2002). Circumglobal (Fricke et al. 2020); close to Alaska off Dixon Entrance, northern British Columbia (Love et al. 2005) to Chile (Pequeño 1989). Depth: 366–2,500 m (1,200 –8,200 ft) (min.: Peden and Hughes 1986; max.: Personal communication: Scripps Institution of Oceanography Fish Collection, La Jolla, California). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 40, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...